A relação paciente-médico: percepções e experiências de pacientes usuários do sistema de saúde de Foz do Iguaçu (2020 a 2022) - Chavez, Christian Roberto (2022)
The research have to analyze the perceptions and experiences of patients in Foz do Iguazu- PR, between 2020 and 2022, in relation to the doctors, seeking to identify factors that reflect their symbolism and representativeness within society as well as to assess whether these factors have altered the patientdoctor relationship over the last decades and, in particular, the last two years in which the pandemic pandemic covid-19 has settled in the world. Therefore, based on bibliographic research on the methods of scientific research, the conception of memory was analyzed, as well as a brief history of medicine in Brazil and in the world. The geographic context of the city is also discussed, and allows the apprehension of UBS problems, in general, in which residents experience difficulties that end up interfering in this patient-doctor relationship. As for the methodology, this is qualitative and quantitative research, represented by graphs. Data collection was done through interviews with the authors who access local health services. The questionnaire was made available through the Google Form tool, as of December 23, 2020, in which 25 interviews were obtained. The work, by correlating memory and medical knowledge and its relationship with the patient, allowed to perceive changes in social relations caused by advances technological of this period. Finally, it brought reflections that allow us to understand social phenomena of contemporaneity in order to adapt them to the new scenarios, challenges and possibilities that arise.